Strategies for the increase of aquacultural production in small reservoirs: the Rancho Pioneiro case in Capitão Poço city, Pará state (Research, Society and Development, 2020)
This study aimed to analyze strategies to increasing aquaculture production in small reservoir on the Rancho Pioneiro property, Capitão Poço city, Pará state. The data obtained between June and August 2018 period, through field observations and semi-structured interviews with the owner, by following subjects: selection of land dam area, structural aspects of the reservoir and fish farming management. On the property was found the adoption of four strategies: net tanks adapted for catching fish in the reservoir; cultive species of different eating habits, aiming population control by carnivorous species and organic matter reduction by detritivorous species; variation in the reservoir volume to promote higher concentrations of dissolved oxygen during night; and construction of two spillways to increase the flow within the dammed water body. It was conclude that the use of efficient strategies to increase the productivity of fish farming in small dams should be plan from the construction of the reservoir, through the selection of species to the adoption of traps for the capture of fish raised extensively. Thus, the experience of Rancho Pioneiro can be replicate totally or partially in other projects in the region, without the need for large additional investments, which tends to improve the profitability of the business.